Trends in Retinopathy of Prematurity over 12 Years in a Colorado Cohort. (4th May 2021) - Mehner, Lauren C.; Wagner, Brandie D.; Bol, Kirk A.; Singh, Jasleen K.; Oliver, Scott CN; Patnaik, Jennifer L.; Palestine, Alan G.; McCourt, Emily A.; Mandava, Naresh; Wymore, Erica M.; Lynch, Anne M.
ABSTRACT: Purpose: To determine trends in retinopathy of prematurity (ROP) in a Colorado cohort between 2006 and 2017 and compare trends in risk factors between our cohort and statewide data. Methods: A retrospective cohort study was conducted by the use of records from two registry databases: 1) an academic center's ROP registry, and 2) vital statistics birth data from the Colorado Department of Public Health and Environment (CDPHE). ROP was categorized as severe (type 1 or type 2), low grade (not type 1 or type 2), or no ROP. Other variables included in the analyses were gestational age and birth weight at delivery, and infant mortality. Trends over time were evaluated for both registry databases using generalized linear models. Results: In our ROP registry cohort of 1, 267 eligible infants, 134 (10.6%) developed severe ROP and 279 (22%) developed low-grade ROP. We found no overall trend in severe ROP rates ( p = .23), and a decreasing trend in rates of low-grade ROP ( p < .01) over the study period. Trends in gestational age, birth weight, and mortality rates remained stable during the study period in both the ROP registry and the CDPHE cohorts. Conclusion: The rate of severe ROP in our ROP registry cohort did not change over time. There was evidence of a decreasing trend in low grade ROP during the 12-year study period that was not explained by a change in the primary ROP risk factors in either the ROP registry cohort or the Colorado statewide data.